Optimization of flowing parts of gas turbines taking into account modes of operation within the limits of system of the automated designing "Turbine unit" - Бойко, А.В.; Говорущенко, Ю.Н.; Усатый, А.П.; Руденко, А.С. (Eastern-European Journal of Enterprise Technologies, 2010)
The multilevel algorithm of optimization of gasturbine installations turbines flow paths taking into consideration operation modes was developed. The basic capabilities and fields of application of the developed algorithm are shown. Optimal design of the low pressure turbine flow path of installation GT-750-6M was performed.